Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Milk lactopeptide alleviates marginal zinc deficiency-associated gut-immune disturbances in rats: associations with barrier-related signaling and gut microbiota - Qi Xin; Xuemin Wang; Sufang Duan; Ruonan Wang; Zifu Zhao; Guofang Zhang; Libo Liu; Peng Du; Chun Li; Jian He (Food Research International, 2026)

Self-supporting, binder-free NiCoAl-LTH/NF composite electrodes for high-efficiency membrane-free capacitive deionization - Ya-Qi Jiang; Yun-Ze Qiu; Chun-Miao Zhang; Qin Li; Jing-Jing Feng; Wen-Qing Fei; Xue-Fei Sun (Desalination, 2026)

CAZyme-resolved substrate routing explains limited soil organic carbon gains under no-tillage in paddy soils - Qi Liu; Xiang-Bin Yao; Yong-Yu Liang; Chun-Yan Li; Xing Wang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2026)

High-surface-area g-C3N4/ZIF-8 heterojunction for synergistic radical and non-radical photocatalytic peroxymonosulfate activation toward antibiotic degradation: Mechanistic insight and membrane application - Ying-Ying Zhang; Si-Han Guo; Wu-He Ji Pi; Qing-Tong Dong; Qi Huang; Jing Bu; Li-Xuan Kou; Chun Li; Quan-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Intelligent theranostic nanoplatforms in next-generation precision oncology - Xiangying Deng; Chun Jiang; Ye Li; Qi Su; Kangling Xie; Lin Zhao (Chemical Engineering Journal, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Complete genome sequence of a novel Pseudomonas sp. GW-45 isolated from Antarctic Ardley cove showing DMSP degradation capability - Yi-He Zhang; Yong-Qiang Hu; Zuo-Qi Wang; Chun-Yang Li; Ting Hu; Zhong Hu; Yin-Xin Zeng (Marine Genomics, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Simulating Martian Atmospheric Processes and Local Dust Events with a Global Variable-Resolution Model (iAMAS-Mars) - Yongxuan Zhao; Chun Zhao; Lulu Li; Li Dong; Jiawang Feng; Jun Gu; Gudongze Li; Chao Wang; Qi Chen (Advances in Atmospheric Sciences, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Three new ent -kaurene diterpenoid glucosides from the flowers of Inula japonica Thunb. - Zheng Niu; Jia-Qi Chen; Guan-Ke Liu; Li-Qin Ding; Chun-Yan Chen; Bing-Yang Zhang; Yu-Hong Li; De-Qin Zhang; Tie Yao; Feng Qiu (Natural Product Research, 2026)

Granulosa cell dysfunction is associated with MCU-mediated mitochondrial calcium dyshomeostasis and reduced AKT phosphorylation in porcine cystic follicles - Yan-Zhu Chen; Ya-Nan Sun; Bo-Qi Zhang; Jin-Xin Zong; Yu-Xin Luo; Si-Hui Wang; Ya-Qiu Li; Hong Hao; Xu Zhou; Lu Chen; Chun-Jin Li (Theriogenology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Iteration in the evolution of hinge teeth in the cementing bivalve families Prospondylidae and Plicatulidae: Evidence from Persia (Nyalamia) n. subgen. from the lowest Jurassic of Xizang (Tibet) - Jia-Hao Li; Michael Hautmann; Qian-Qi Zhang; Hai-Chun Zhang; Jin-Geng Sha (Palaeoworld, 2026)

A soil freezing characteristic model considering the tortuous structure and complex distribution of soil pores - Jianyuan Zhao; Shuangyang Li; Qi Jiang; Minqi Dong; Chun Bao; Shangqi Zhou; Huiyin Liu (Journal of Hydrology, 2026)

Fenugreek gum/casein edible gel film based on polycarboxylic acid cross-linking: Performance characterization, cross-linking mechanism and application - Shengnan Liang; Jia Song; Tianhang Zheng; Guofang Zhang; Chun Li; Libo Liu; Peng Du; Xiaoxi Qi; Zhicheng Chen; Quan Su; Jiazhou Wei (Food Chemistry, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Lactobacillus helveticus KLDS 1.1105 postbiotics alleviate functional constipation through gut microbiota modulation - Jiaying Liu; Miao Li; Qi Xin; Chun Li; Aili Li; Guofang Zhang; Ruihong Yu; Peng Du; Libo Liu (Food Bioscience, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Transcriptomic analysis reveals organ-specific adaptations in the gut-liver axis during diet domestication of mandarin fish (Siniperca chuatsi) - Hao-Yu Li; Zhi-Guang Hou; Yi-Huan Xu; Cheng-Bin Wu; Zun-Li Qi; Xiao-Wei Gao; Chun‑Long Zhao; Xin Zhao; Li-Han Zhang (Aquaculture International, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Associations of Fluke (Spirorchiid) Infection and Buoyancy Disorder with Death in Stranded Sea Turtles Undergoing Rehabilitation in Taiwan - Ming-An Tsai; I-Chun Chen; Pei-Qi Ye; Po-Yu Wu; Tsung-Hsien Li (Journal of Marine Science and Engineering, 2026)
Sea turtles are increasingly regarded as indicators of coastal ecosystem health, as their clinical condition and disease profiles reflect prolonged exposure to environmental pressures in impacted marine habitats. Wildlife rehabilitation facilities play an important role in sea turtle conservation, although risk factors associated with mortality during rehabilitation are not well defined. This retrospective study evaluated clinical and infectious risk factors for death in 108 stranded sea turtles (including 70 green turtles, 19 olive ridley turtles, 16 hawksbill turtles, 2 loggerhead turtles, and 1 leatherback turtle) admitted to the rehabilitation facility at the National Museum of Marine Biology and Aquarium between 2018 and 2024. Data on buoyancy disorder, spirorchiid fluke infection, fibropapillomatosis and final disposition were analysed using univariate and multivariable logistic regression. Buoyancy disorder (adjusted OR = 9.96) and spirorchiid fluke infection (adjusted OR = 3.33) were associated with increased mortality, highlighting the need for careful monitoring and early detection of these conditions during rehabilitation. However, the retrospective design may inherently limit causal inference.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Catalytic co-pyrolysis of furfural residue and polypropylene for value-added co-production of hydrogen, sustainable aviation fuel fractions, and carbon nanotubes - Junhao Hu; Nianxiang Qi; Huijuan Tian; Yang Du; Shanzhi Xin; Haiping Yang; Shaomei Zhi; Zhijuan Chen; Chun Chang; Shusheng Pang; Pan Li (Biomass and Bioenergy, 2026)

Selenylation enhances anti-melanogenic activity of polysaccharide from Cinnamomum cassia Presl. by regulating the CREB/MITF/tyrosinase pathway - Qi-Cong Chen; Ya-Li Wang; Yu Luo; Yan-Ling Zhang; Wen-Xin Li; Wei-Feng Cai; Qian Ni; Cui-Ping Jiang; Qiang Liu; Chun-Yan Shen (Food Research International, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Three-dimensional cell culture in vitro could better recapitulate the biological behavior of cells in vivo - Zhihao Qi; Shuhua Yang; Chun Fu; Junjie Xu; Quan Li; Junfang Yan; Aihua Shen; Burong Hu (Tissue and Cell, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Structure characteristics of a pectic polysaccharide from the leaves of Cornus officinalis Sieb. et Zucc. (Shanzhuyu) and its inhibition on hepatocellular carcinoma - Yu-Xuan Gao; Sheng-Wei Hu; Nan Wang; Shu-Yao Wang; Na Liu; Xiao-Qiang Li; Qi-Mei Duan; Yan-Chun Qi; Wei Cao (Carbohydrate Polymers, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

Multifunctional whey protein composite films: Material design and AI integration for next-generation food packaging - Qi Xin; Meishuai Liu; Ruonan Wang; Peng Du; Jia Song; Libo Liu; Chun Li; Qi Wang; Yongping Bao (Trends in Food Science & Technology, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Cost-effective one-pot preparation of nanoporous phenolic resins for efficient CH4 purification from C1-C3 light hydrocarbons in natural gas - Gen Li; Chun-Jie Yuan; Yong-Qi Li; Qi-Hong Mei (Fuel, 2026)

Study on Aeromagnetic Anomaly Characteristics and Tectonic Ore-Controlling Effects in Leiwuqi-Zuogong Area, Tibet - Jian-chun Xu; Yan-xu Liu; Wen-yong Li; An-qi Cao; Shan Gao; Xue Yang (Applied Geophysics, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Heterointerface-dominated MoO3@Fe2(MoO4)3 nanorods with oxygen vacancy for boosting trace trimethylamine detection - Dan Meng; Lijun Li; Lei Zhang; Ruixiang Li; Jian Qi; Chun He; Xiaoguang San (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Multiscale interface engineering via femtosecond laser synergized with micro-Ag interlayer for robust ceramic-metal sintered-joining in protonic ceramic fuel cells - Naiqiang Wang; Xiaoqing Si; Hanyue Ding; Zhihu Zhang; Jianwei Gao; Shaletanati Ake; Xuexue Li; Chun Li; Junlei Qi; Jian Cao (Chemical Engineering Journal, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

The evolution and research hotspots of perfluorinated compounds (PFCs): Health risks, environmental behavior, and collaborative effort - Jing-Xuan Zhou; Xiong-Bo Liu; Zi-Yi Zheng; Li-Chun Qiao; Yi Hu; Kaiyao Hu; Xuming Liu; Xiang Jia; Wenhao Qi (Journal of Environmental Chemical Engineering, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Impaired Synaptic Plasticity Mediated by Decreased GLUT1 in Hippocampal Astrocytes is Involved in Postoperative Cognitive Dysfunction in Elderly Mice - Zi-Yi Li; Qiang Liu; Xiao-Tian Shi; Xin-Hao Jiao; Yue Zhou; Chen Chen; Wei-Feng Wu; Wei Dong; Yong-Kang Qiu; Yi-Qi Liu; Chun-Hui Jin; Ao Sun; et al. (Molecular Neurobiology, 2025)

First report on trait segregation in F1 hybrids between the cultivated peanut (Arachis hypogaea L.) and the wild incompatible species A. glabrata Benth. - Wei Jie Qi; Hao Jie Sun; Jing Yu; Chun Jiao Jiang; Guang Di Yuan; Shang Xia Li; Chun Yan Xu; Chuan Tang Wang (Genetic Resources and Crop Evolution, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Diversity oriented synthesis of cyano-substituted polycyclic N-heteroaryl compounds in green solvent - Yuan-Qi Li; Zhi-Jie Kang; Ben-Jun Han; Yan-Chun Zhang; Fan Teng; Cheng-Tao Feng (Sustainable Chemistry and Pharmacy, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Nitrogen form-driven shifts in microbial community and nitrogen cycling of microplastic surface biofilms - Yu Zheng; Liying Qi; Liangliang Dai; Yan Song; Shuangshuang Li; Chun Wang (Process Safety and Environmental Protection, 2025)

Organophosphate esters and their transformation products in megacity atmospheres: Size-dependent gas-particle partitioning and transformation potential - Chun-Xue Tang; Min-Qi Tang; Chen-Chou Wu; Cheng Li; Ming-Hong Cai; Lian-Jun Bao; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

Cultured biomass enhances the flavor and nutrition characteristics of biomass/plant hybrid cultured meatballs - Zi-Qing Meng; Chang-Bo Tang; Tian-yi Tao; Wenjuan Song; Chun-Bao Li; Jun Qi; Shi-jie Ding; Guang-Hong Zhou (Food Research International, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Mulberry Diels-Alder-type adducts and other phenolic compounds with ATP-citrate lyase inhibitory effects from Morus alba and their chemotaxonomic significance - Qi Zhou; Ying-Peng Tong; Jiang Wan; Li-Hong Yan; Chun-Xiao Jiang; Jin-Feng Hu (Biochemical Systematics and Ecology, 2025)

The microbiome, metabolome, and correlation analysis reveal the beneficial role of the commensal Shewanella sp. MR-7 in foodborne enteritis in turbot (Scophthalmus maximus L.) - Chao-Qun Li; Wen-Yi Wang; Xin Wen; Si-Yu Qi; Jia-Ning Xu; Dan-Yu Wu; Kang-Di Tian; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Adaptive changes of biofilm and sludge in CANON process under various organics stresses: Performance, biomass characteristics and metabolic pathways - Ben-ze Chang; Yi-chun Zhao; Shuai Zhang; Qi Luo; Dong-zhi Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Process Safety and Environmental Protection, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Milk-derived exosome nanovesicles: recent progress and daunting hurdles - Kaili Wang; Xu Zhao; Sijia Yang; Xiaoxi Qi; Guofang Zang; Chun Li; Aili Li; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2025)

High levels of fishmeal replacement with torula yeast reduces growth, negatively affects hepatic and intestinal health, and intestinal microbiota of largemouth bass (Micropterus salmoides) - Ze Sheng Zhang; Zhi Li Ding; Meng Ting Wang; Dong Chun Li; Wen Qi Chen; Shun Yang; Hui Fei (Aquaculture, 2025)

Mechanochemical synthesis of ZnS-based sepiolite composites for accommodation of gaseous mercury from coal-fired flue gas - Chun-Gang Yuan; Miao Bian; Shuo Liu; Li-Qi Li; Fan-Chen Liu; Qi Guo; Shiwei Guo; Xue-Lei Duan (Journal of Environmental Chemical Engineering, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

High-Precision Sub-Seafloor Velocity Building Based on Joint Tomography and Deep Learning on OBS Data in the South China Sea - Guoxin Chen; Jun Li; Jinxin Chen; Rongsen Du; Yutao Liu; Yuli Qi; Chun Feng Li; Xingguo Huang (Journal of Earth Science, 2025)

Increase of ATP synthesis and amino acids absorption contributes to cold adaptation in Antarctic bacterium Poseidonibacter antarcticus SM1702T - Wen-Yue Xu; Sha-Sha Liu; Xiao-Han Guo; Peng Wang; Chun-Yang Li; Li Liao; Qi-Long Qin (Extremophiles, 2025)

Elemental Imbalances After Manganese Exposure and the Regulatory Potential of Curcumin - Hua Zhao; Jia-Min Zeng; Yao Li; Chun-Yan Ao; Duo Liu; Jing-Peng Zhuo; Chun Yu; Jia-Qi Ban; Jun Li (Biological Trace Element Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Understanding the role of land attachment in the emergence of hollow villages based on the agent-based complex system framework - Qi Zhang; Cai Jin; Jing Cao; Jing Hu; Chun Dai; Richard E. Bilsborrow; Tan Li; Conghe Song (Land Use Policy, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Dual Channel passivation enhancing stable perovskite Light-Emitting diodes - Shao-Qi Wang; Wei Yang; Yu Xia; Bin Wang; Nan Li; Lei Huang; Xin Chen; Yu-Han Li; Jing Chen; Chun-Hao Chen; Zhao-Kui Wang (Chemical Engineering Journal, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Fast ion transport network enhanced 3D Zn anode for ultra-stable zinc ion batteries - Qi Li; Guizhou Liu; Shixiang Zhou; Sihan Tang; Ruiying Luo; Peng Wei; Chun Fang; Chunze Yan (Chemical Engineering Journal, 2025)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

A new fulgoroidian insect (Hemiptera: Surijokocixiidae) from the Middle Triassic Tongchuan Formation of northwestern China - Qian-Qi Zhang; Lan Li; Jacek Szwedo; Tong Bao; Hai-Chun Zhang (Palaeoworld, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Comprehensive comparison of water quality risk and microbial ecology between new and old cast iron pipe distribution systems - Youyi Chen; Huishan Zhou; Hui Gao; Ziliang Su; Xinjun Li; Peng Qi; Tong Li; Chun Hu; Zesong Li; Zhihao Bi; Xueci Xing; Jingxin Yang; et al. (Journal of Environmental Sciences, 2024)

Insight into the mechanism of alkyl polyglucose biosurfactants enhancing antibiotics resistance genes removal during biotransformation of waste activated sludge into medium-chain fatty acids - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Sheng-qiang Fan; Wan-li Ma; Nan-qi Ren (Chemical Engineering Journal, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Immune responses in giant groupers after vaccination with inactivated bivalent vaccine against betanodavirus and ranavirus - Yu-Hsuan Kai; Chun-Kuei Chang; Hong-Qi Li; Wei-Hsu Chen; Shau-Chi Chi; Yu-Chi Wu (Aquaculture, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Enhancing medium-chain fatty acids production via alkyl polyglucose modulation of electron acceptor generation, microbial community and metabolic traits in anaerobic fermentation of waste activated sludge - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Guo-jun Xie; Wan-li Ma; Sheng-qiang Fan; Nan-qi Ren (Chemical Engineering Journal, 2024)

Phytochemical constituents from rhizomes of Dryopteris crassirhizoma and their anti-inflammatory activity - Xiao-Jun Li; Xiong-Hui Song; Si-Qi Tang; Kai-Xin Wei; Zong-Wu Suo; Yi Xu; Jiao Luo; Hao Huang; Chun-Ying Li; Dong-Xu Liu; Xiang-Qian Liu (Natural Product Research, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

Multiple strategy for antibacterial effect via copper porphyrin doping polyphenolic aldehydes based covalent organic framework - Zi-Wen Zhou; Chun-Xiu Liu; Chun-Xian Cai; Yun-Jie Wei; Kun Li; Xiao-Qi Yu; Yan-Hong Liu; Na Wang (Journal of Environmental Chemical Engineering, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Probing the AFF4–CCNT1 protein–protein interaction using a metal–organic conjugate for treating triple-negative breast cancer - Ying-Qi Song; Yiwen Xu; Li-Jun Yang; Ling Wang; Shaozhen Jing; Guan-Jun Yang; Daniel Shiu-Hin Chan; Chun-Yuen Wong; Wanhe Wang; Vincent Kam Wai Wong; Chung-Hang Leung (Chemical Engineering Journal, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Deciphering the reduction of antibiotic resistance genes (ARGs) during medium-chain fatty acids production from waste activated sludge: Driven by inhibition of ARGs transmission and shift of microbial community - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Wei Liu; Wan-li Ma; Nan-qi Ren (Journal of Hazardous Materials, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Cross-scale analysis on the mechanical behavior of the conglomerate of Yulin Grottoes in China - Huihui Zhang; Qinglin Guo; Yanwu Wang; Shibin Tang; Tianjiao Li; Qi Zhang; Chun'an Tang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

Unlocking the mystery of Tibetan yak butter and its byproducts: Processing, physicochemical characteristics, functional benefits, and applications - Guofang Zhang; Jinwei Sun; Jingbo Yang; Xiaoxi Qi; Ramnarain Ramakrishna; Qiming Li; Wengkui Guo; Chun Li; Libo Liu; Peng Du; Wei Yu; Bingcan Chen (Trends in Food Science & Technology, 2024)

Activation of RXRα exerts cardioprotection through transcriptional upregulation of Ndufs4 in heart failure - Mingyan Shao; Lingru Li; Lin Ma; Chao Song; Weili Li; Yawen Zhang; Wenkun Cheng; Yun Chen; Ye Yang; Qian Wang; Chun Li; Qi Wang; et al. (Science Bulletin, 2024)

Transcriptome analysis reveals vanadium reduction mechanisms in a bacterium of Pseudomonas balearica - Chun-dan Gan; Jin-yan Yang; Jiang-fei Li; Meng-qi Yang; Xin-yue Du; Aleksander Nikitin (Journal of Cleaner Production, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Bio-based adsorption foam composed of MOF and polyethyleneimine-modified cellulose for selective anionic dye removal - Zihui Yuan; Feng Li; Xuefeng Zhang; Mei-Chun Li; Yan Chen; Cornelis F. de Hoop; Jinqiu Qi; Xingyan Huang (Environmental Research, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Climatic factors and fertilization rates co-regulate anaerobic methane oxidation driven by multiple electron acceptors in Chinese paddy fields - Wang-ting Yang; Wei-qi Wang; Evgenios Agathokleous; Ya-nan Bai; Shuai Zhang; Chun Wang; Yan-fang Feng; Jia-qi Liu; Yu-ling Yang; Cai-yu Geng; Li-dong Shen (Journal of Cleaner Production, 2024)

The central Qiangtang Metamorphic Belt in northern Tibet is an in-situ Paleo-Tethys Ocean: Evidence from newly discovered Late Devonian radiolarians - Xin Li; Noritoshi Suzuki; Yi-chun Zhang; Hua Zhang; Mao Luo; Dong-xun Yuan; Quan-feng Zheng; Wen-kun Qie; Qi Ju; Feng Qiao; Hai-peng Xu; Xiao-hui Cui (Gondwana Research, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Review on the gentle hydrometallurgical treatment of WPCBs: Sustainable and selective gradient process for multiple valuable metals recovery - Xi-guang Li; Qiang Gao; Si-qi Jiang; Chun-chen Nie; Xiang-nan Zhu; Tian-tian Jiao (Journal of Environmental Management, 2023)

A method to predict the peak shear strength of rock joints based on machine learning - Li-ren Ban; Chun Zhu; Yu-hang Hou; Wei-sheng Du; Cheng-zhi Qi; Chun-sheng Lu (Journal of Mountain Science, 2023)

A deep learning approach for object detection of rockfish in challenging underwater environments - Mingxin Liu; Wencheng Jiang; Mingxin Hou; Zihua Qi; Ruixin Li; Chun Zhang (Frontiers in Marine Science, 2023)
Introduction Preserving the marine ecological environment and safeguarding marine species is a global priority. However, human overfishing has led to a drastic decline in fish species with longer growth cycles, disrupting the equilibrium of the marine ecosystem. To address this issue, researchers are turning to deep learning techniques and state-of-the-art underwater devices, such as underwater robots, to explore the aquatic environment and monitor the activities of endangered populations. This approach has emerged as a focal point of recent research in protecting the marine ecological environment. This study employs a deep learning-based object detection algorithm to identify fish species in complex underwater environments. Methods The algorithm is built upon the You Only Look Once version 7(YOLOv7) algorithm, with the addition of the attention mechanism Convolutional Block Attention Module (CBAM) in the network’s backbone. CBAM enhances the feature maps through the fusion of spatial attention and channel attention, ultimately improving the robustness and accuracy of the model’s inference by replacing the original loss function CIoU with SCYLLAIntersection over Union(SIoU). In this paper, the rockfish pictures in the dataset Label Fishes in the Wild published by the National Marine Fisheries Service are selected, and the underwater image enhancement model (UWCNN) is introduced to process the pictures. Result The experimental results show that the mean average precision (mAP) value of the improved model on the test set is 94.4%, which is 3.5% higher than the original YOLOv7 model, and the precision and recall rate are 99.1% and 99%, respectively. The detection performance of the algorithm in the field of complex underwater environment is improved. Discussion The underwater fish detection scheme proposed in this study holds significant practical value and significance in promoting the conservation of marine ecosystems and the protection of fish species.

Constructing electrochemical sensor using molecular-imprinted polysaccharide for rapid identification and determination of l-tryptophan in diet - Yan-Jun Li; Li-Li Yang; Li Ni; Jia-Min Xiong; Jia-Yuan He; Lian-Di Zhou; Ling Luo; Qi-Hui Zhang; Chun-Su Yuan (Food Chemistry, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Vanadium mobilization and redistribution during mineral transformation of vanadium-titanium magnetite tailings with different weathering degrees - Chun-dan Gan; Jin-yan Yang; Xin-yue Du; Jia-li Li; Qi-xuan Tang; Aleksander Nikitin (Science of The Total Environment, 2023)

Surface characteristic driven in waste printed circuit boards flotation: Floatability mechanism of resin and glass fiber in non-metallic component - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xian-jun Lyu; Ya-qing Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

N-doped carbon dots coupled with molecularly imprinted polymers as a fluorescent sensor for ultrasensitive detection of genistein in soya products - Yu-Zhen Zhang; Bo Zhang; Qing-Qing Chen; Lan Qin; Ya-Qi Hu; Chun-Hua Bai; Yi-Le Li; Bei Qin (Food Chemistry, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Time-programmed activation of CD47 disruption and immunogenic cell death with Cas9 ribonucleoprotein nanocapsule for improved cancer immunotherapy - Yumeng Xing; Jianhui Yang; Chun Wang; Ziyao Kang; Zheng Pan; Jihui Tang; Fenghe Li; Xiao Wang; Xiao-ming Meng; Zhifei Cheng; Yang Liu; Qi Liu (Chemical Engineering Journal, 2023)

Biocompatible snowman-like tumor-targeting dimer nanoparticles for improved delivery efficiency and enhanced anti-tumor therapy - Chanqi Ye; Xiaoxiao Yan; Xiaomeng Dai; Ruyin Chen; Qiong Li; Shuaishuai Xu; Qi Jiang; Feifei Yan; Suzhen Xu; Chun-Xia Zhao; Peng Zhao; Dong Chen; et al. (Chemical Engineering Journal, 2023)

Efficient immobilization and detoxification of gaseous elemental mercury by nanoflower/rod WSe2/halloysite composite: Performance and mechanisms - Xuelei Duan; Yuan Li; Changxian Zhao; Yiwen Shen; Qi Guo; Zhihao Huang; Dexu Shan; Yue Gao; Kegang Zhang; Jianbo Shi; Jingfu Liu; Yongsheng Chen; et al. (Journal of Hazardous Materials, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

MicroRNA‑30a‑5p regulates cypermethrin-induced apoptosis of Sertoli cells by targeting KLF9 in vitro - Qi Wang; Jia-Fei Xie; Ting-Ting Yao; Xu-Xu Wang; Qian-Wen Guo; Lu-Shan Wang; Yue Yu; Li-Chun Xu (Reproductive Toxicology, 2023)

Phytoecdysteroids from Dianthus superbus L.: Structures and anti-neuroinflammatory evaluation - Xue-Li Hou; Yu-Qi Gao; Jing-Hui Yang; Han-Wu Liu; Meng-Meng Bai; Zhen-Hai Wu; Chun-Huan Li; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2023)

Decoupling analysis to assess the impact of land use patterns on carbon emissions: A case study in the Yellow River Delta efficient eco-economic zone, China - Qian Wang; Chuan-hao Yang; Ma-li Wang; Lin Zhao; Yu-chen Zhao; Qi-peng Zhang; Chun-yan Zhang (Journal of Cleaner Production, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

The future for biochemical recycling of poly(ethylene terephthalate): From lab to process - Chun-Chi Chen; Xian Li; Panpan Shen; Yunyun Yang; Jian Min; Qi Zhang; Yingle Liu; Jian-Wen Huang; Rey-Ting Guo (Current Opinion in Green and Sustainable Chemistry, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Population analysis reveals the roles of DNA methylation in tomato domestication and metabolic diversity - Hao Guo; Peng Cao; Chao Wang; Jun Lai; Yuan Deng; Chun Li; Yingchen Hao; Zeyong Wu; Ridong Chen; Qi Qiang; Alisdair R. Fernie; Jun Yang; et al. (Science China Life Sciences, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Removal of antibiotic resistant bacteria and genes by nanoscale zero-valent iron activated persulfate: Implication for the contribution of pH decrease - Chun-shuang Zhou; Guang-li Cao; Xiu-Kun Wu; Bing-feng Liu; Qing-Yue Qi; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Facile fabrication of Fe/Zr binary MOFs for arsenic removal in water: High capacity, fast kinetics and good reusability - Qi Guo; Yuan Li; Li-Wei Zheng; Xiao-Yang Wei; Yan Xu; Yi-Wen Shen; Ke-Gang Zhang; Chun-Gang Yuan (Journal of Environmental Sciences, 2023)

The effect of methanol atmosphere and/or H-ZSM-5 catalyst on the thermal upgrading of volatiles generated from Hami lignite pyrolysis - Yun-xin Ma; Yue-lun Wang; Xu Yan; Gui-gui Zhan; Wen-Qi Li; Xue-chun Zhang; Jing-pei Cao (Fuel, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Biodegradation of isobutyraldehyde with high removal efficiency by using a modified biotrickling filter - Tao Gu; Yunhui Li; Qingdian Yin; Chun Miao; Bo Zhang; Zhiyong Xie; Kang Wang; Shengping You; Wei Qi; Rongxin Su (Journal of Environmental Chemical Engineering, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Seasonal variations of airborne phthalates and novel non-phthalate plasticizers in a test residence in cold regions: Effects of temperature, humidity, total suspended particulate matter, and sources - Chun-Yan Huo; Wen-Long Li; Li-Yan Liu; Yu Sun; Jia-Qi Guo; Liang Wang; Hayley Hung; Yi-Fan Li (Science of The Total Environment, 2023)

Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat - Yang Liu; Chun-Li Qi; Da-Wei Li; Hong-Ye Li; Rui-Man Li; Wei-Dong Yang (Food and Chemical Toxicology, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

Enhancements of dissociation of electrode materials in spent lithium-ion batteries by low-temperature heating pretreatment - Si-qi Jiang; Chun-chen Nie; Shun-xiang Shi; Yong-qiang Zhao; Xiang-guang Li; Chao-zhu Deng; Lu Yang; Ling Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

Low-cost, high-density Mn–Co spinel coatings for stainless steel interconnect via efficient microwave heating - Xiaoyang Wang; Xiaoqing Si; Jianwei Gao; Qihan Zhou; Chun Li; Mingshen Li; Junlei Qi; Jian Cao (Journal of Cleaner Production, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

Abundant and diverse endophytic bacteria associated with medicinal plant Arctium lappa L. and their potential for host plant growth promoting - Jia-Qi Liu; Shu-Mei Chen; Chun-Mei Zhang; Ming-Jie Xu; Ke Xing; Cheng-Guo Li; Kui Li; Yu-Qin Zhang; Sheng Qin (Antonie van Leeuwenhoek, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Identifying the spatiotemporal characteristics of individual red bed landslides: a case study in Western Yunnan, China - Xin Zhao; Guo Li; Zhi-fang Zhao; Chun-xiao Li; Qi Chen; Xian Ye (Journal of Mountain Science, 2022)

Kai-Xin-San Inhibits Tau Pathology and Neuronal Apoptosis in Aged SAMP8 Mice - Ya-Nan Jiao; Jing-Sheng Zhang; Wen-Jun Qiao; Shu-Yu Tian; Yi-Bin Wang; Chun-Yan Wang; Yan-Hui Zhang; Qi Zhang; Wen Li; Dong-Yu Min; Zhan-You Wang (Molecular Neurobiology, 2022)
Alzheimer’s disease (AD) is an age-related neurological disorder. Currently, there is no effective cure for AD due to its complexity in pathogenesis. In light of the complex pathogenesis of AD, the traditional Chinese medicine (TCM) formula Kai-Xin-San (KXS), which was used for amnesia treatment, has been proved to improve cognitive function in AD animal models. However, the active ingredients and the mechanism of KXS have not yet been clearly elucidated. In this study, network pharmacology analysis predicts that KXS yields 168 candidate compounds acting on 863 potential targets, 30 of which are associated with AD. Enrichment analysis revealed that the therapeutic mechanisms of KXS for AD are associated with the inhibition of Tau protein hyperphosphorylation, inflammation, and apoptosis. Therefore, we chose 7-month-old senescence-accelerated mouse prone 8 (SAMP8) mice as AD mouse model, which harbors the behavioral and pathological hallmarks of AD. Subsequently, the potential underlying action mechanisms of KXS on AD predicted by the network pharmacology analyses were experimentally validated in SAMP8 mice after intragastric administration of KXS for 3 months. We observed that KXS upregulated AKT phosphorylation, suppressed GSK3β and CDK5 activation, and inhibited the TLR4/MyD88/NF-κB signaling pathway to attenuate Tau hyperphosphorylation and neuroinflammation, thus suppressing neuronal apoptosis and improving the cognitive impairment of aged SAMP8 mice. Taken together, our findings reveal a multi-component and multi-target therapeutic mechanism of KXS for attenuating the progression of AD, contributing to the future development of TCM modernization, including KXS, and broader clinical application. Graphical abstract

Effects of dihydroartemisinin, a metabolite of artemisinin, on colon cancer chemoprevention and adaptive immune regulation - Chong-Zhi Wang; Chunping Wan; Yun Luo; Chun-Feng Zhang; Qi-Hui Zhang; Lina Chen; Zhi Liu; Daniel H. Wang; Mallory Lager; Cang-Hai Li; Ting-Liang Jiang; Lifei Hou; et al. (Molecular Biology Reports, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Ecdysis Triggering Hormone, Eclosion Hormone, and Crustacean Cardioactive Peptide Play Essential but Different Roles in the Molting Process of Mud Crab, Scylla paramamosain - Yan-Fei Zhao; Qi-Qiao Wen; Chun-Mei Ao; Wei Wang; Li-Li Shi; Cheng-Gui Wang; Siuming-Francis Chan (Frontiers in Marine Science, 2022)
Molting behavior in insects is controlled by the ecdysis triggering hormone (ETH), eclosion hormone (EH) and the crustacean cardioactive peptide (CCAP). At present, the regulation of molting behavior in crustaceans remains unclear. Here, we studied the roles of ETH , EH , and CCAP in the molt regulation of the crab, Scylla paramamosain from their expression pattern and in vivo assays. The results showed that transcripts of ETH , EH , and CCAP were mainly localized in thoracic ganglia and fluctuated periodically with the molting cycle. When ETH or CCAP was knockdown at early premolt stage (D0), molting of crabs was interrupted and all animals died at late premolt stage (D2). While the EH gene was knock-down, most crabs were dead before D2. Injection of synthetic peptide for ETH or CCAP rescued ETH - or CCAP -gene knock-down crabs separately. However, none of peptides could rescue dsEH -injected crabs. At D0 stage, knockdown of ETH down-regulated the transcriptions of EH and CCAP ; while ETH was up-regulated when EH was knockdown. At D2 stage, ETH transcripts levels were reduced with the injection of dsEH but increased with the same dose of dsETH as crabs at D0 stage. Co-injection of ds ETH and ds EH down-regulated ETH at D2 stage. Results showed that ETH , EH , and CCAP play essential but different roles in molt regulation in mud crab. In summary, the result of this study contributes to the discovery of different molecular mechanisms between Insecta and Crustacea and may provide insight to develop fishery drugs that helps aquacultured crustaceans to molt successfully.

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Ethylene insensitive mutation alleviates cadmium-induced photosynthesis impairment in Arabidopsis plants - Qi-Yu Zhao; Chun-Xiu Gu; Yu Wang; Guang-Zhe Li; Lin Hao (Acta Physiologiae Plantarum, 2022)

A new indole alkaloid from the stems of Glycosmis puberula var . craibii - Qi Zhou; Chun-Xiao Jiang; Shou-Yuan Wu; Zi-Ming Chen; Li-Ping Huang (Natural Product Research, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Abnormal meiosis in fertile and sterile triploid cyprinid fish - Chun Zhang; Qi Li; La Zhu; Wangchao He; Conghui Yang; Hui Zhang; Yu Sun; Luojing Zhou; Yuandong Sun; Shurun Zhu; Chang Wu; Min Tao; et al. (Science China Life Sciences, 2021)

Time-resolved Fluorescence Immunoassay (TRFIA) for the Simultaneous Detection of MMP-9 and Lp-PLA2 in Serum - Hong-yan Ma; Qian Mao; Yan-bin Zhu; Chun-li Cong; Shi-yu Zheng; Qi Zhang; Cui-cui Chen; Lai-qing Li (Journal of Fluorescence, 2021)

The relationship between diabetes-related cognitive dysfunction and leukoaraiosis - Chun-lan Yuan; Ran Yi; Qi Dong; Li-fen Yao; Bin Liu (Acta Neurologica Belgica, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Maternal exposure to O3 and NO2 may increase the risk of newborn congenital hypothyroidism: a national data-based analysis in China - Cuifang Qi; Li Shang; Wenfang Yang; Liyan Huang; Liren Yang; Juan Xin; Shanshan Wang; Jie Yue; Lingxia Zeng; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Maternal exposure to air pollution during pregnancy is associated with adverse outcomes in the offspring, but limited studies focused on the impacts of gaseous air pollution on newborn congenital hypothyroidism (CH). Therefore, a national data-based analysis was conducted to explore the association between maternal exposure to gaseous air pollution and the incidence of CH in China. Annual average exposure levels of SO 2 , NO 2 , CO, and O 3 from January 1, 2014, to December 30, 2014, were acquired from the Chinese Air Quality Online Monitoring and Analysis Platform. The annual incidence of newborn CH from October 1, 2014, to September 30, 2015, was collected from the Chinese Maternal and Child Health Surveillance Network. Temperature and toxic metal in wastewater in 2014 were also collected as covariates. Maternal exposure to O 3 and NO 2 in 1 μg/m 3 level increment was positively associated with newborn CH, with an OR of 1.055 (95% CI 1.011, 1.102) and 1.097 (95% CI 1.019, 1.182) after adjusting for covariates completely. Compared with the lowest level of O 3 , maternal exposure to the 4th quartile of O 3 was positively associated with newborn CH (OR 1.393, 95% CI 1.081, 1.794) after adjusting for covariates completely. And the 3rd and 4th quartiles of NO 2 were associated positively with CH (OR 1.576, 95% CI 1.025, 2.424, and OR 1.553, 95% CI 0.999, 2.414, respectively) compared with the lowest level of NO 2 . By fitting the ROC curve, 93.688 μg/m 3 in O 3 might be used as cutoff to predict the incidence of newborn CH in China.

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Neuromodulation-Based Stem Cell Therapy in Brain Repair: Recent Advances and Future Perspectives - Ti-Fei Yuan; Yi Dong; Li Zhang; Jieyu Qi; Chun Yao; Yongjun Wang; Renjie Chai; Yan Liu; Kwok-Fai So (Neuroscience Bulletin, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Least-squares reverse time migration method using the factorization of the Hessian matrix - Sun Xiao-Dong; Teng Hou-Hua; Ren Li-Juan; Wang Wei-Qi; Li Zhen-Chun (Applied Geophysics, 2021)

Impact of air pollution exposure during various periods of pregnancy on term birth weight: a large-sample, retrospective population-based cohort study - Li Shang; Liyan Huang; Liren Yang; Longtao Leng; Cuifang Qi; Guilan Xie; Ruiqi Wang; Leqian Guo; Wenfang Yang; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Previous studies have suggested that maternal exposure to air pollution might affect term birth weight. However, the conclusions are controversial. Birth data of all term newborns born in Xi’an city of Shaanxi, China, from 2015 to 2018 and whose mother lived in Xi’an during pregnancy were selected form the Birth Registry Database. And the daily air quality data of Xi’an city was collected from Chinese Air Quality Online Monitoring and Analysis Platform. Generalized additive models (GAM) and 2-level binary logistic regression models were used to estimate the effects of air pollution exposure on term birth weight, the risk term low birth weight (TLBW), and macrosomia. Finally, 321521 term newborns were selected, including 4369(1.36%) TLBW infants and 24,960 (7.76%) macrosomia. The average pollution levels of PM 2.5 , PM 10 , and NO 2 in Xi’an city from 2015 to 2018 were higher than national limits. During the whole pregnancy, maternal exposure to PM 2.5 , PM 10 , SO 2 , and CO all significantly reduced the term birth weight and increased the risk of TLBW. However, NO 2 and O 3 exposure have significantly increased the term birth weight, and O 3 even increased the risk of macrosomia significantly. Those effects were also observed in the first and second trimesters of pregnancy. But during the third trimester, high level of air quality index (AQI) and maternal exposure to PM 2.5 , PM 10 , SO 2 , NO 2 , and CO increased the term birth weight and the risk of macrosomia, while O 3 exposure was contrary to this effect. The findings suggested that prenatal exposure to air pollution might cause adverse impacts on term birth weight, and the effects varied with trimesters and pollutants, which provides further pieces of evidence for the adverse effects of air pollution exposure in heavy polluted-area on term birth weight.

Inclination effect of coal mine strata on the stability of loess land slope under the condition of underground mining - Xue-yang Sun; Chun-Hsing Ho; Cheng Li; Yucheng Xia; Qi Zhang (Natural Hazards, 2020)

Occurrence and partitioning of brominated flame retardants (BFRs) in indoor air and dust: a 15-month case study in a test home - Jia-Qi Guo; Yong-feng Li; Li-Yan Liu; Chun-Yan Huo; Yu Sun; Wan-li Ma; Zi-feng Zhang; Yi-Fan Li (Environmental Science and Pollution Research, 2020)

Identification and expression profiling analysis of ascorbate peroxidase gene family in Actinidia chinensis (Hongyang) - Guang-Lian Liao; Qing Liu; Yi-Qi Li; Min Zhong; Chun-Hui Huang; Dong-Feng Jia; Xiao-Biao Xu (Journal of Plant Research, 2020)

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis - Li Shang; Liren Yang; Wenfang Yang; Liyan Huang; Cuifang Qi; Zixuan Yang; Zhuxuan Fu; Mei Chun Chung (Environmental Science and Pollution Research, 2020)
The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children’s cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient was extracted, conversed, and synthesized by random effects meta-analysis. Meanwhile, qualitatively describe would be used for some studies which cannot be synthesized quantitatively for lack of quantity or methods inconsistency. Finally, a total of 3848 citations were searched, and only 10 studies were included. We estimated that per 10 μg/m 3 increase of NO 2 during pregnancy was associated with a − 0.76 point decrease in global psychomotor (95% CI, − 1.34, − 0.18) and a − 0.62 point decrease in fine psychomotor for children (95% CI, − 1.09, − 0.16). But no significant association found in general cognitive and language. In addition, through the literature review, it seemed that prenatal exposure to NO 2 might cause adverse impacts on children’s attention, IQ, and different behaviors, but this requires confirmation from further researches. Our study indicated that prenatal exposure to NO 2 seems to be associated with impaired neural development for children, especially for fine psychomotor. However, further studies are needed for determining the effects of prenatal air pollution exposure on attention, IQ, and behavior.

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Correction to: Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2020)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

MdHIR4 transcription and translation levels associated with disease in apple are regulated by MdWRKY31 - Xian-Yan Zhao; Chen-Hui Qi; Han Jiang; Ming-Shuang Zhong; Chun-Xiang You; Yuan-Yuan Li; Yu-Jin Hao (Plant Molecular Biology, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2019)

Apple AP2/EREBP transcription factor MdSHINE2 confers drought resistance by regulating wax biosynthesis - Ya-Li Zhang; Chun-Ling Zhang; Gui-Luan Wang; Yong-Xu Wang; Chen-Hui Qi; Chun-Xiang You; Yuan-Yuan Li; Yu-Jin Hao (Planta, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Thimet oligopeptidase and prolyl endopeptidase of spotted scat Scatophagus argus: characterization, tissue distribution, expression at different ovarian stages and down-regulation by estradiol - Si-ping Deng; Dong-neng Jiang; Jian-ye Liu; Zhi-qi Liang; Hua-pu Chen; Tian-li Wu; Chun-hua Zhu; Guang-li Li (Fisheries Science, 2018)

The vanadium isotopic composition of L ordinary chondrites - Yongli Xue; Chun-hui Li; Yuhan Qi; Chuantong Zhang; Bingkui Miao; Fang Huang (Acta Geochimica, 2018)

Physiological response to salinity stress and tolerance mechanics of Populus euphratica - Chun Yan Zhao; Jian Hua Si; Qi Feng; Ravinesh C. Deo; Teng Fei Yu; Pei Du Li (Environmental Monitoring and Assessment, 2017)

Toxicity comparison of different active fractions extracted from radix Sophorae tonkinensis in zebrafish - Hong-cui Liu; Xiao-yu Zhu; Jiang-hua Chen; Sheng-ya Guo; Chun-qi Li; Zhong-ping Deng (Journal of Zhejiang University-SCIENCE B, 2017)

Dating of the topmost terrace in the Jingxian Basin, Anhui Province: an indication of the establishment of the Qingyijiang River - Chun-sheng Hu; Chen-qi Hu; Shao-chen Liu; Guang-lai Xu; Li Wu; Li-hui Yang (Journal of Mountain Science, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Captopril improves postresuscitation hemodynamics protective against pulmonary embolism by activating the ACE2/Ang-(1-7)/Mas axis - Hong-Li Xiao; Chun-Sheng Li; Lian-Xing Zhao; Jun Yang; Nan Tong; Le An; Qi-Tong Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

Erratum to: NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

Detection of Vulnerable Atherosclerotic Plaques in Experimental Atherosclerosis with the USPIO-Enhanced MRI - Chun-mei Qi; Lili Du; Wei-heng Wu; Dong-ye Li; Ji Hao; Lei Gong; Liangrong Deng; Tao Zhang; Chao Zhang; Yu Zhang (Cell Biochemistry and Biophysics, 2015)

Meiotic chromosome configurations in triploid progeny from reciprocal crosses between wild-type diploid and natural tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Jia-Qi Li; Katsutoshi Arai (Genetica, 2015)

Heat stress inhibits proliferation, promotes growth, and induces apoptosis in cultured Lantang swine skeletal muscle satellite cells - Chun-qi Gao; Yin-ling Zhao; Hai-chang Li; Wei-guo Sui; Hui-chao Yan; Xiu-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Growth of embryo and gene expression of nutrient transporters in the small intestine of the domestic pigeon (Columba livia) - Ming-xia Chen; Xiang-guang Li; Jun-xian Yang; Chun-qi Gao; Bin Wang; Xiu-qi Wang; Hui-chao Yan (Journal of Zhejiang University-SCIENCE B, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

The pulse of imperial C hina: a quantitative analysis of long‐term geopolitical and climatic cycles - David D. Zhang; Qing Pei; Harry F. Lee; Jane Zhang; Chun Qi Chang; Baosheng Li; Jinbao Li; Xiaoyang Zhang (Global Ecology and Biogeography, 2015)
Aim The long‐term cyclical patterns of C hina's geopolitical shifts are of great interest to scholars and the public, but to date there has been no satisfactory explanation for the alternating occupancy patterns of the country's pastoral and agrarian polities. We fill this gap by differentiating the agroecological settings of these polities over time and quantitatively analysing the relationships between climate change and historical geopolitical variations. Location C hina. Methods Our dataset comprised 38 palaeohydroclimate reconstructions, the historical boundaries of C hina's empire and the changes in its size, and 1028 wars and 2737 battle locations over the past 2300 years. C hina‐wide precipitation during the period was reconstructed using the ‘weighted composite plus scale’ method. Time‐series analyses were performed to identify the strength of the associations between climate change and the geopolitical variables. Granger causality analysis and wavelet analysis were performed to verify the hypothesized causal links. Wavelet analysis was also used to identify the possible interactions (i.e. frequencies, significance, consistency and synchrony) between the signal components of the climatic and geopolitical variables at different temporal scales. Results C hina's mean precipitation fell into three multicentennial cycles. The geopolitical variables corresponded to those cycles in the imperial era. The spatial–temporal frequencies of the boundaries and size of the agriculturalist empires and its frontiers with pastoralist empires were regulated by the long‐term (low‐frequency) precipitation fluctuations at the multicentennial scale. Wars of aggression were an important explanatory factor driving the land‐occupancy patterns of the two ecoempires under climate change, and caused most of the territorial shifts. Short‐term (high‐frequency) geopolitical changes were not associated with climate change. Main conclusions Precipitation‐induced ecological change was an important factor governing the macrogeopolitical cycles in imperial C hina. Long‐term territorial expansion favoured the polity (agriculturalist or pastoralist) that was better adapted to the changing ecological conditions in the country's heartland.

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Assessment of chlorpyrifos exposure and absorbed daily doses among infants living in an agricultural area of the Province of Jiangsu, China - Ping Liu; Chun-hua Wu; Xiu-li Chang; Xiao-juan Qi; Ming-lan Zheng; Zhi-jun Zhou (International Archives of Occupational and Environmental Health, 2014)

Interaction network analysis revealed biomarkers in myocardial infarction - Tong Zhang; Li-Li Zhao; Zhuo-Ran Zhang; Pei-De Fu; Zhen-Dong Su; Li-Chun Qi; Xue-Qi Li; Yu-Mei Dong (Molecular Biology Reports, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Fast determination of sulfonamides and their acetylated metabolites from environmental water based on magnetic molecularly imprinted polymers - Haiyan Chen; Yiqun Zhang; Bo Gao; Yang Xu; Qi Zhao; Juan Hou; Jin Yan; Guijie Li; Hui Wang; Lan Ding; Jie Ding; Chun Zhao (Environmental Science and Pollution Research, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Isolation and characterization of three fungi with the potential of transforming glycyrrhizin - Chao Wang; Xiao-Xiao Guo; Xiao-Yan Wang; Feng Qi; Shi-Jiang Feng; Chun Li; Xiao-Hong Zhou (World Journal of Microbiology and Biotechnology, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

The modulation of venlafaxine on cortical activation of language area in healthy subjects with fMRI study - Qi Xie; Yan Liu; Chun-Yong Li; Xue-Zhu Song; Jun Wang; Li-Xin Han; Hong-Min Bai (Psychopharmacology, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Involvement of CtBP2 in LPS-induced microglial activation - Guowei Zhang; Yaohua Yan; Lihua Kang; Qi Cao; Kaifu Ke; Xinmin Wu; Yilu Gao; Qinglei Hang; Chunmiao Li; Lin Zhu; Qin Yuan; Qiyun Wu; et al. (Journal of Molecular Histology, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Relative bioavailability and pharmacokinetic comparison of two different enteric formulations of omeprazole - Jian Liu; Jian-zhong Shentu; Li-hua Wu; Jing Dou; Qi-yang Xu; Hui-li Zhou; Guo-lan Wu; Ming-zhu Huang; Xing-jiang Hu; Jun-chun Chen (Journal of Zhejiang University-SCIENCE B, 2012)

Deletion of RBP-J in adult mice leads to the onset of aortic valve degenerative diseases - Zhi Li; Lei Feng; Chun-Mei Wang; Qi-Jun Zheng; Bi-Jun Zhao; Wei Yi; Jin-Zhou Zhang; Yue-Min Wang; Hai-Tao Guo; Ding-Hua Yi; Hua Han (Molecular Biology Reports, 2012)

Gene expression profiles of two intraspecific Larix lines and their reciprocal hybrids - Ai Li; Meng-Die Fang; Wen-Qin Song; Cheng-Bin Chen; Li-Wang Qi; Chun-Guo Wang (Molecular Biology Reports, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Forest stand biomass estimation using ALOS PALSAR data based on LiDAR-derived prior knowledge in the Qilian Mountain, western China - Qi-Sheng He; Chun-Xiang Cao; Er-Xue Chen; Guo-Qing Sun; Fei-Long Ling; Yong Pang; Hao Zhang; Wen-Jian Ni; Min Xu; Zeng-Yuan Li; Xiao-Wen Li (International Journal of Remote Sensing, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Interpolation of near offset using surface-related multiples - Shu-Juan Guo; Zhen-Chun Li; Zhao-Qi Tong; Fang-Zheng Ma; Jian-Hui Liu (Applied Geophysics, 2011)

A neural-network model to retrieve CDOM absorption from in situ measured hyperspectral data in an optically complex lake: Lake Taihu case study - De Yong Sun; Yun Mei Li; Qiao Wang; Heng Lu; Cheng Feng Le; Chang Chun Huang; Shao Qi Gong (International Journal of Remote Sensing, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Molecular identification of endophytic fungi from medicinal plant Huperzia serrata based on rDNA ITS analysis - Xu Yu Chen; Yao Dong Qi; Jian He Wei; Zheng Zhang; De Li Wang; Jin Dong Feng; Bing Chun Gan (World Journal of Microbiology and Biotechnology, 2011)

Pigment epithelium-derived factor plays an inhibitory role in proliferation and migration of HaCaT cells - Chun-Ming Li; Wei Li; Xiao-Yong Man; Jiong Zhou; Jia-Qi Chen; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2011)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Developing new SSR markers from ESTs of pea (Pisum sativum L.) - Ya-ming Gong; Sheng-chun Xu; Wei-hua Mao; Qi-zan Hu; Gu-wen Zhang; Ju Ding; Ya-dan Li (Journal of Zhejiang University-SCIENCE B, 2010)

N2O fluxes from the native and grazed semi-arid steppes and their driving factors in Inner Mongolia, China - Xing-Ren Liu; Yun-She Dong; Yu-Chun Qi; Sheng-Gong Li (Nutrient Cycling in Agroecosystems, 2010)

An intimate coupling of ocean–atmospheric interaction over the extratropical North Atlantic and Pacific - Chun Li; Lixin Wu; Qi Wang; Liwei Qu; Liping Zhang (Climate Dynamics, 2009)

DETA/NONOate, a nitric oxide donor, produces antidepressant effects by promoting hippocampal neurogenesis - Yao Hua; Xin-Yan Huang; Li Zhou; Qi-Gang Zhou; Yao Hu; Chun-Xia Luo; Fei Li; Dong-Ya Zhu (Psychopharmacology, 2008)

Inhibition by oxytocin of methamphetamine-induced hyperactivity related to dopamine turnover in the mesolimbic region in mice - Jia Qi; Jing-Yu Yang; Ming Song; Yan Li; Fang Wang; Chun-Fu Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A recombinant pseudorabies virus co-expressing capsid proteins precursor P1-2A of FMDV and VP2 protein of porcine parvovirus: a trivalent vaccine candidate - Qi Hong; Ping Qian; Xiang-Min Li; Xiao-Lan Yu; Huan-Chun Chen (Biotechnology Letters, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Development of a Latex Agglutination Test Using The Major Epitope Domain of Glycoprotein E of Pseudorabies Virus Expressed in E. coli to Differentiate Between Immune Responses in Pigs Naturally Infected or Vaccinated with Pseudorabies Virus - Tang Yong; Chen Huan-chun; Xiao Shao-bo; Qin Ya-li; He Qi-gai; Ren Yu-qi (Veterinary Research Communications, 2005)

Evaluation of genetic diversity and germ plasm identification of 44 species, clones, and cultivars from 5 sections of the genusPopulus based on amplified fragment length polymorphism analysis - Chun Jiang Zhou; Hong Zhu Song; Jin Hua Li; Jian Wei Sun; Min De Jin; Qi Wen Zhang; Bin Wang (Plant Molecular Biology Reporter, 2005)

A study on the mechanism and character of the industrial and spatial transference of FDI in China - Guo-ping Li; Kai-zhong Yang; Qi-chun He; Tie-shan Sun (Chinese Geographical Science, 2001)